Ex Vivo Anatomical Characterization of Handsewn or Stapled Jejunocecal Anastomosis in Horses by Computed Tomography Scan - Giusto, Gessica (J Vet Med, 2014)
The aim of this study is to compare handsewn and stapled jejunocecal anastomosis with different stomal lengths in terms of anatomical differences. Group 1 underwent a two-layer handsewn jejunocecal side-to-side anastomosis (HS); Group 2 received a stapled jejunocecal side-to-side anastomosis (GIA). Each group was divided into two subgroups (HS80 and HS100, GIA80 and GIA100). Specimens were inflated and CT scanned. The stomal/jejunal area ratio and blind end pouch volume/area were measured and compared. Effective length of the stoma was measured and compared with the initial length. Stomal/jejunal area ratio was 1.1 for both 80 techniques, 1.6 for the GIA100, and 1.9 for the HS100 technique. Both HS and GIA techniques produced a blind end pouch and exhibited a mean increase of the final stomal length ranging from 6 to 11% greater than the original stomal length. All techniques will exhibit a length increase of the final stomal length compared to the intended stomal length, with a consequent increase in stomal area. Stapled techniques consistently produced a large distal blind end pouch. Length of a jejunocecal anastomosis should be selected in accordance with the diameter of afferent jejunum, and the 80 mm stomal length could be deemed sufficient in horses.